Performance of LDPC Codes in Multipath OFDM System - Wahyuningrum, Reni Dyah; Hafiza, Lia; Ni’amah, Khoirun; Larasati, Solichah; Udlhiya, Ida (Journal of Telecommunication Electronics and Control Engineering (JTECE), 2025)
In fifth-generation wireless networks (5G), a significant challenge arises: delivering high-speed data transmission and extensive networking services while maintaining a low bit error rate (BER). To meet the demands of 5G services, Orthogonal Frequency Division Multiplexing (OFDM) emerges as a promising technique for ensuring high-quality communication and an FFT size of 256. Moreover, several channel coding methods have been employed to enhance BER performance. Among these methods, Quasi Cyclic- Low-Density Parity Check (QC-LDPC) has become the established standard for high-speed data transmission in 5G networks. However, implementing these coding methods in conjunction with 5G standard specifications presents various complexities and challenges. In this research, we analyze QC-LDPC in multipath fading using OFDM. The performance of QC-LDPC codes at a BER of 10-3 can be achieved with an SNR of 15 dB for OFDM with QC-LDPC codes and an SNR of 20 dB for OFDM. The inclusion of QC-LDPC coding in the OFDM system significantly improves performance by reducing the required SNR for a BER of 10-3 from 20 dB (uncoded) to 15 dB (coded), a 5 dB reduction. Channel coding with QC-LDPC also enhances system efficiency by consistently decreasing the BER across various SNR values. These results confirm that QC-LDPC coding provides better reliability and performance than the uncoded OFDM system.